Variable Environments in an Upwelling System Trigger Differential Thermal Sensitivity in a Low Intertidal Chiton - Manríquez, Nahomi; Bacigalupe, Leonardo D.; Lardies, Marco A. (Frontiers in Ecology and Evolution, 2021)
Environmental variability in coastal oceans associated with upwelling dynamics probably is one of the most pervasive forces affecting the physiological performance of marine life. As the environmental temperature is the abiotic factor with major incidence in the physiology and ecology of marine ectotherms, the abrupt temperature changes in upwelling systems could generate important variations in these organisms’ functional processes. The relationship between ambient temperature and physiological performance can be described through a thermal performance curve (TPC). The parameters of this curve usually show geographic variation usually is in accordance with the predictions of the climate variability hypothesis (CVH), which states that organisms inhabiting more variable environments should have broader ranges of environmental tolerance in order to cope with the fluctuating environmental conditions they experience. Here we study the effect generated by the environmental variability in an active upwelling zone on the physiological performance of the marine ectotherm Achanthopleura echinata. In particular, we compared the parameters of the TPC and the metabolic rate of two populations of A. echinata, one found in high semi-permanent upwelling (Talcaruca), while the other is situated in an adjacent area with seasonal upwelling (Los Molles) and therefore more stable environmental conditions. Our results show that: (1) oxygen consumption increases with body size and this effect is more significant in individuals from the Talcaruca population, (2) optimal temperature, thermal breadth, upper critical limit and maximum performance were higher in the population located in the area of high environmental heterogeneity and (3) individuals from Talcaruca showed greater variance in optimal temperature, thermal breadth, upper critical limit but not in maximum performance. Although it is clear that a variable environment affects the thermal physiology of organisms, expanding their tolerance ranges and generating energy costs in the performance of individuals, it is relevant to note that upwelling systems are multifactorial phenomena where the rise of water masses modifies not only temperature, but also decreases O2, pH, and increases pCO2 which in turn could modify metabolism and TPC.